The Impact of Land Conversion as a Form of Industrialization on the Community Life in Pantura (Faculty of Social Science, Universitas Negeri Semarang, 2022)
As a developing country, Indonesia continues to strive to increase its level to become a developed country in new ways, one of which is industrialization. Industrialization is predicted to able to improve the welfare of people's lives and open up many new jobs for the community. However, various industrialization practices that have been and will be carried out are, in fact, not in favor of the community and instead create conflicts and social inequality in society. One of the industrializations carried out in Indonesia is one along the North Coast of Java or Pantura. This study aims to find out how industrialization is from the government and the capital owners’ perspectives and the real impact of industrialization on society. This study uses a qualitative approach. Data were collected in the form of video documentaries and literature studies. The study results show that industrialization does not favor the welfare of society. Many people are put in a difficult situation because of the loss of lands and livelihoods and the environmental damage caused by industrialization. With this, it can be seen that industrialization is not following people's needs, aspirations, and desires.